Succession in Shorea robusta Forests of Uttar Pradesh - Srivastava, P. B. L. (Indian Forester, 1964)
Succession studies in various communities of sal forests of Uttar Pradesh indicate that so far as the trends in secondary succession are concerned, the two communities of dry facies, viz., Terminalia-Ehretia-Lagerstroemia and Ehrctia-Lagerstroemia-Cassia represent parallel retrogression stages, conditioned by edaphic and biotic factors, both of which on adequate protection will tend to evolve into the Lagerstroemia-Ehretia community. On further deterioration of the site conditions, these communities will degrade to dry mixed deciduous forest without sal and ultimately to short savannah. The three communities of moderately dry facies occupy different positions on the successional gradient. Lagerstroemia-Enretia is the most stable community. Terminalia-Lagerstroemia- Bridelia community represents rather a lower stage towards the drier end. On deterioration of conditions it will regress to dry mixed deciduous forest without sal while if progression sets in, it will tend towards Lagerstroemia-Ehretia community. On the contrary, Terminalia-Syzygium-Cordia community represents a higher stage in progression than the Lagerstroemia-Ehretia community which on further improvement will progress towards Taminalia-Syzygium-Litsaea community while on regression it will tend towards Terminalia-Lagerstroemia-Bridelia community. Terminalia-Syzygium-Litsaea community of the moist facies represents rather a climax stage under the prevailing conditions. However, if left undisturbed, it will attain a postclimax stage in which the proportion of evergreen components, especially in lower strata, will increase at the expense of sal. In view of these facts, in order to improve the stocking of sal and obtain adequate regeneration, it is necessary to resort to silvicultural practices which will help in maintaining the balance in such a way that too much progression, resulting in moist evergreen forest with less proportion of sal or excessive retrogression resulting in deciduous forest devoid of sal, is prevented. The probable trends of primary succession leading to the formation of closed sal forests have also been described in detail.